Simulating Carbon Markets - Carbon Pricing Leadership Coalition (World Bank, Washington, DC, 2020)
Carbon market simulations are programs, models, virtual environments, and/or games that allow stakeholders to participate in a simulated process of designing or participating in an ETS. They are a low-cost and low-risk option of building capacity for both policymakers and regulated companies. The experiential learning processes these tools enable serves to increase ETS literacy, helps build support for ETS as a policy option, and illustrates how policy outcomes are a function of design. Importantly, ETS simulations can provide an opportunity for different stakeholdersto build relationships, mutual understanding and trust, all of which are key prerequisites for working together on policy design and implementation. Finally, these tools provide stakeholders with a safe and risk-free opportunity to try out new ideas, make mistakes, and to learn lessons which can serve to speed the adoption of effective ETSs.